2010
DOI: 10.1080/19398441.2010.488031
|View full text |Cite
|
Sign up to set email alerts
|

The influence ofmarianismobeliefs on physical activity of mid‐life immigrant Latinas: a Photovoice study

Abstract: Various explanations have been proposed to explain the low levels of physical activity among Latinas. Included is the construct marianismo, which describes the influence of cultural beliefs on gender role identity, including prioritisation of familial responsibilities over self-care. The purpose of the study was to explore the influence of marianismo beliefs on participation in habitual and incidental physical activity among middle-aged immigrant Hispanic women, using a community- based participatory research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Familismo or the belief in family unity as being of greater importance than the individual and marianismo or the belief in the importance of meeting responsibilities toward others may combine to negatively influence Latinas participation in LTPA (D'Alonzo & Fischetti, 2008;D'Alonzo & Sharma, 2010). Marianismo beliefs and economic factors may also combine to negatively influence Latinas' PA engagement (D'Alonzo & Sharma, 2010). Consistent with these cultural influences is our finding that the main effect of family living arrangements on engagement in PA is the difference between single adult households and all others.…”
Section: Discussionsupporting
confidence: 72%
“…Familismo or the belief in family unity as being of greater importance than the individual and marianismo or the belief in the importance of meeting responsibilities toward others may combine to negatively influence Latinas participation in LTPA (D'Alonzo & Fischetti, 2008;D'Alonzo & Sharma, 2010). Marianismo beliefs and economic factors may also combine to negatively influence Latinas' PA engagement (D'Alonzo & Sharma, 2010). Consistent with these cultural influences is our finding that the main effect of family living arrangements on engagement in PA is the difference between single adult households and all others.…”
Section: Discussionsupporting
confidence: 72%
“…However, this lifestyle is not an economic reality for most immigrant Latinas. In a study of mid-life immigrant women, D’Alonzo and Sharma (2010) reported that the Latinas in a Photovoice study took on a series of low paying jobs in order to finance their children’s college tuition, a situation the authors referred to as the “ nuevo marianismo .” Lorch (1996) noted it is when Latin American women immigrate to the US that contradictions in values become apparent and cultural conflicts can occur. Findings from the LIP Study suggest that marianismo beliefs are but one of a constellation of interrelated social and cultural factors which combine to adversely influence the physical activity behaviors of immigrant women.…”
Section: Discussionmentioning
confidence: 99%
“…Keller & Fleury (2006) reported Hispanic and African- American women responded negatively to the term “leisure time” and often viewed leisure time as a luxury. D’Alonzo and Sharma (2010) have noted that the term evokes an elitist mindset which is not consistent with the lifestyles of most immigrant women. Some Latinos, particularly those with low acculturation levels, feel that most types of physical activity and sport are unfeminine (D’Alonzo & Fischetti, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similar methodological concerns arose in the author’s Photovoice study. Although the use of photovoice can itself be seen as a type of empowerment intervention (D’Alonzo and Sharma in press), the author was concerned about the subjects’ acceptance of the camera as a data collection method among immigrants. As a result, preparatory sessions were held with the subjects to address ethical issues associated with the use of photovoice, including what and who to photograph and measures to minimize invasion of privacy.…”
Section: Research Project – Methodological Issuesmentioning
confidence: 99%
“…The author and her nursing students became frequent visitors to the CBO and participated in invited social activities there. Three years later, the author approached the CBO about initiating a small qualitative Photovoice study at the site (D’Alonzo and Sharma in press). By that time, she was familiar with the community’s assets and needs and had taken the time to establish trust and credibility among community members who were familiar with the CBO.…”
Section: The ‘Pre‐research’ Periodmentioning
confidence: 99%